Gender Equality among Women in West Klampis Village, Bangkalan Regency:Feminist Perspective - Nur Wahyuni; Dewi Casmiwati (Journal of Feminism and Gender Studies, 2024)
The community in this village still adheres to a patriarchal culture where men are the main authority in the family. Most parents in this village also assume that a woman's job is to take care of her husband and children and to do housework. A woman is required to be able to cook, clean the house, wash clothes and so on. It is also not uncommon for parents to refuse to continue their children's education to a higher level. This research was conducted to analyze and describe gender equality in West Klampis Village, Klampis District, Bangkalan Regency. This research uses descriptive research with a qualitative approach. The focus of this research is gender equality in terms of the theory of liberal feminism by Mary Wollstonecraft and Marxist feminism by Karl Marx and Friedrich Engels. Data obtained through observation, interviews and documentation. The results showed that in liberal feminism, women experience inequality in education that is not equal to men, while in Marxist feminism, there is a class between wives and husbands in the household, where a wife's class is reproductive while a husband's class is productive.